2011
DOI: 10.1007/s00234-011-0958-8
|View full text |Cite
|
Sign up to set email alerts
|

Detecting damaged regions of cerebral white matter in the subacute phase after carbon monoxide poisoning using voxel-based analysis with diffusion tensor imaging

Abstract: VBA demonstrated that CO-poisoned patients with chronic neurological symptoms had already suffered damage to various CWM regions in the subacute phase. In these regions, the centrum semiovale was suggested to be the main region damaged in the subacute phase after CO inhalation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…48,59 Our previous study in which we used DTI with voxelbased analysis also showed that deep WM areas including the centrum semiovale were the most widely damaged regions in those patients presenting with chronic symptoms (Fig 4). 60 When the CO-damaged brain is assessed by DWI or DTI, it is important to emphasize that evaluations of deep WM, including the centrum semiovale, are indispensable.…”
Section: 40mentioning
confidence: 99%
“…48,59 Our previous study in which we used DTI with voxelbased analysis also showed that deep WM areas including the centrum semiovale were the most widely damaged regions in those patients presenting with chronic symptoms (Fig 4). 60 When the CO-damaged brain is assessed by DWI or DTI, it is important to emphasize that evaluations of deep WM, including the centrum semiovale, are indispensable.…”
Section: 40mentioning
confidence: 99%
“…However, it is well known that the subacute phase is an important phase that indicates a risk of developing DNS in patients after CO exposure, and that WMD is highly associated with the occurrence of DNS9101219. Therefore, we hypothesized that BT is associated with WMD in patients with CO-poisoning.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, patients who presented delayed neuropsychiatric sequelae (DNS) showed remarkable BT reduction of >1 °C between the acute and subacute phases. It has been well known that the occurrence of DNS was highly associated with cerebral white matter damage (WMD) caused by progressive demyelination after CO inhalation910111213; thus, BT in patients with CO-poisoning may potentially be associated with the degree of WMD, which can affect brain metabolism. Thus, the aim of the present study was to investigate whether the BT in patients with CO-poisoning was associated with the degree of WMD in the subacute phase.…”
mentioning
confidence: 99%
“…Indeed, some studies have reported correlations between FA values in various regions of the CWM in the chronic phase and cognitive dysfunction among CO-poisoned patients with DNS [16, 23, 30]. However, the centrum semiovale in the CWM has been suggested as a key region responsible for chronic neurological symptoms [4, 10, 19, 22]. A study using DTI at various phases after CO poisoning has also shown that FA in the centrum semiovale changes in parallel with cognitive impairments or neurological symptoms [17].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, FA is frequently used for evaluating the extent of damaged CWM fibers in patients with demyelinating diseases such as multiple sclerosis [1, 27]. CO poisoning causes damage in various regions of the CWM, but the centrum semiovale has been considered a region more responsible for chronic neuropsychiatric symptoms after CO poisoning than other regions [4, 10, 19, 22]. Herein, we measured FA from DTI at the centrum semiovale in CO-poisoned patients, and evaluated the correlation between the FA and concentration of MBP in the CSF.…”
Section: Introductionmentioning
confidence: 99%